Peran Sistem Pengendalian Internal, Kompetensi Aparatur Desa dan Budaya Organisasi terhadap Pencegahan Kecurangan Dana Desa - Safitri, Dewi Ayu; Khikmah, Siti Noor; Pramita, Yulinda Devi (Universitas Muhammadiyah Metro, 2025)
This research aims to empirically test the influence of the internal control system, village apparatus competence and organizational culture on preventing fraud in managing village funds. The research population was all village officials in 20 Wndusari District village offices. The sampling technique used purposive sampling consisting of the village head, secretary, treasurer and planning head. The research sample was 73 respondents. Data analysis used SPSS version 26. The results of this research show that the internal control system has a positive effect on preventing fraud in managing village funds, while the competence of village officials and organizational culture have not effect on preventing fraud in managing village funds